The Study of a Kazakh document in Chinese archives related to Khankhoja sultan’s cattle trade and its historical significance - Abdilashim, D. (Karaganda University named after academician E.A.Buketov, 2023)
In the following article, Advanced research methods of history and historical philology are used, along with a letter written by the Kazakh’s sultan Khankhoja, who owned the East Kazakh steppe since the end of the 18th century and had close relations with the neighboring Qing dynasty, to the local taiji who was in charge of affairs in Tarbagatai is studied. The letter is written in the old Kazakh written language, the language is simple, understandable, the content is deep, it is an original document written by the Kazakh, which is very valuable for the comprehensive study of the trade business of the Kazakh steppe. In the previous studies, it was often said that “silk was traded for horses”, but as we can see from the content of the analyzed letter, not only horses were exchanged for silk, sometimes other livestock were also traded. The letter is now stored in the First Historical Archives of China in Beijing. From the contents of the letter, the long history of Kazakh- Kyrgyz relations can be indirectly understood.
Ханқожа сұлтанның мал саудасына байланысты Қытай архивіндегі қазақ құжатың зерттеу және оның тарихи маңызы
Исследование казахского документа в китайских архивах, связанного с торговлей скотом Ханходжи султана, и его историческое значение
Keywords: Kazakh Khanate; East Kazakh steppe; Qing Dynasty; Khankhoja sultan; cattle trade; Chinese archives; Kazakh document; historical significance